WFP Innovation Accelerator: contracting report and country action plans - Karunakaran, K.; Al-Zu’bi, Maha; Qui, Z.; Michalscheck, Mirja; Hulbert, S.; Kamanda, Josey; Quadri, S.; Nkosi, Mahlatse; Craparo, A. (International Water Management Institute (IWMI). CGIAR Initiative on Fragility, Conflict, and Migration, 2024)
This report outlines the due diligence process, grant formalization, Innovation Packing and Scaling Readiness (IPSR) workshops, and action plans for the innovations selected in the Stability-and-Peace Accelerator cohort. The due diligence process assessed both the operational and financial soundness of the innovators, screening for legal and reputational risks via international databases, and evaluating financial stability through key indicators like liquidity and debt-to-equity ratios. After formalizing grant agreements, IPSR workshops were held in Jordan, Nigeria, and Kenya, in collaboration with IWMI, ABC and IITA, to gather feedback and enhance the scalability of the innovations. These workshops facilitated discussions on improving water security, refining product designs, and enhancing conflict prediction tools. Innovators like AquaPoro, iPlant, Koolboks, and Conflict Forecast received specific guidance on cost efficiency, market entry strategies, and user-centered design improvements. Action plans, developed with input from country focal points, outlined milestones and KPIs to validate scalability and feasibility, ensuring progress is tracked. Overall, these steps have laid a foundation for scaling impactful solutions in fragile settings, fostering resilient food and water systems while promoting sustainable business models in refugee host communities.